Low cost thermic system for transfusable substance improving - BRAUN Barbu Criatian; DRUGĂ Corneliu Nicolae; ȘERBAN Ionel; MITU Leonard (My University, 2024)
The paper presents a stage of research regarding the design, development and testing of a flexible, low-cost system that allows improving the process of transfusion of vital substances. It is primarily about the process of heating and bringing them to an optimal temperature from the point of view of thermal biocompatibility for the beneficiary. From the implementation point of view, the heating solution proved to be an effective one both in terms of process duration and in reducing energy consumption. Regarding the functional testing, the method of recording and measuring the temperature values of transfusable substances using an infrared thermal imaging camera was used. Based on the results related to temperature measurement, finding values very close to the ideal ones specific to such processes, it was possible to conclude that the method is efficient, reliable, low-cost, and it can be implemented in the near future in hospitals and of blood transfusion centers, for all categories of subjects, regardless of the conditions that require a trans-plant.
Keywords: Transfusable Substances; Thermal Imaging Camera; Temperature; Blood; Bio-compatibility